2006
DOI: 10.1021/la053021l
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Luminescent Tellurium Nanowires of Several Nanometers in Diameter and High Aspect Ratio Synthesized by a Poly (Vinyl Pyrrolidone)-Assisted Hydrothermal Process

Abstract: Large-scale selective synthesis of uniform single crystalline tellurium nanowires with a diameter of 4-9 nm, and microbelts with a width of 250-800 nm and tens of micrometers in length, can be realized by a poly (vinyl pyrrolidone) (PVP)-assisted hydrothermal process. The formation of tellurium nanowires and nanobelts in the presence of PVP is strongly dependent on the reaction conditions such as temperature, the amount of PVP, and reaction time. The results demonstrated that the keys for selective synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
255
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(284 citation statements)
references
References 30 publications
(32 reference statements)
22
255
2
3
Order By: Relevance
“…[ 25 ] The well-defi ned Te@C nanocables were obtained by the so-called hydrothermal carbonization (HTC) process from Te nanowires and glucose. [ 26 , 27 ] Removal of the Te cores by chemical etching in a 5% H 2 O 2 solution resulted in the formation of pure ultralong CNFs with uniform diameter (see the Supporting Information (SI) for details).…”
Section: Doi: 101002/adma201001863mentioning
confidence: 99%
“…[ 25 ] The well-defi ned Te@C nanocables were obtained by the so-called hydrothermal carbonization (HTC) process from Te nanowires and glucose. [ 26 , 27 ] Removal of the Te cores by chemical etching in a 5% H 2 O 2 solution resulted in the formation of pure ultralong CNFs with uniform diameter (see the Supporting Information (SI) for details).…”
Section: Doi: 101002/adma201001863mentioning
confidence: 99%
“…To prevent the nanowires from aggregating, the surfactant PVP was used to chemically adsorb onto the surfaces of bismuth nanowires by O-Bi bonding. 23 Many reports 18,24,25 have indicated that PVP had the functions of controlling the growth rates of different crystalline faces and assisting in fabricating the nanowires. However, our work indicates that both nanoparticles and nanowires had been synchronously formed in the assistance of PVP in the lack of bismuth seeds.…”
Section: Resultsmentioning
confidence: 99%
“…These values are close to the reported values for Te nanowires. [20][21][22] The first peak at 270 nm is assumed to result from the allowed transition from the valence band to the conduction band and the second peak at 630 nm can be assigned to a forbidden direct transition. 23 We conducted time-dependent observation of absorption spectra of Te nanowires suspended in the DMEM medium alone and the DMEM growth medium separately.…”
Section: Resultsmentioning
confidence: 99%